Spirituality in entrepreneurship from Islamic perspective - Kedah, Zulkarnain; Mohammed Adamu, Isa (IIUM Press, 2011)
Spirituality in entrepreneurship is an emerging area of interest which has begun to generate attention from management scholars. However, most research carried out in this area is from the western perspective. Until recently, there is dearth of research that gears towards spirituality in Islam and its contribution to the overall development of modern organisations. Precious little information is available regarding spirituality in Islam and its effects on entrepreneurial outcomes. This exploratory study presents a conceptual analysis of the effects of spirituality in Islam on entrepreneurial motivation, performance and commitment to social responsibility. It has been suggested that spirituality in Islam has the potential to positively influence the attitudes of entrepreneurs and to serve as a motivational drive for going into business. Also, it has the potential to serve as a catalyst for positive energy, enhanced performance and increased commitment to social responsibility. Thereafter study presented a conceptual framework based on exhaustive literature reviews, to guide future research, which was subsequently followed with a discussion on the implications for theory and professional practice at the end.